Analysis of stamping dezincification of DP590 alloyed hot dip galvanized dual phase steel. Issue 1 (1st December 2022) - Huang, Geng; Liu, Xueli; Li, Liejun
Abstract: with the requirements of vehicle lightweight and safety performance, dual phase steel is more and more widely used in vehicles. However, the stamping of the sheet has attracted more attention due to the increased use of dual-phase steels in auto parts. In this paper, the surface morphology, composition, surface kinetic friction coefficient, and plate thickness change rate of stamping plates were detected, calculated, and analyzed respectively. Based on solving the problem of the dezincification defect of DP590 alloyed hot-dip galvanized dual-phase steel during stamping. In addition, the stamping die was also investigated and analyzed, The results showed that the stamping die has deteriorated beyond the service life, resulting in the reduction of the adaptability between the die and the material. More importantly, the low Fe content and high dynamic friction coefficient of the surface of the stamped plate made the zinc layer unable to keep up with the tensile deformation of the substrate during stamping, which was the main factor for the lamellar detachment at the interface between the zinc layer and the substrate. By updating the dies and improving the plate design, the stamping dezincification defects of the sheet have basically disappeared.